The Quality Management of Islamic Boarding School Based on Information Technology in the 4.0 Industry Era - Siswanto Siswanto (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
The Islamic boarding school education needs to be well constructed through designing of an education system that is adapted to the demands of educational quality in the current 4.0. industry era. Through qualitative research approach dan data collection technique using indepth interview, observation, and documentation, this research found: Firstly, the quality management of Islamic boarding school based on information technology is based on the idea that Nurul faces a transition period and requires managerial work which is an integral part of all pesantren elements to realize the pesantren's vision and mission, as well as be a pilot project in the quality management based on information technology in the 4.0 industry era, especially in the East Java region. Secondly, to improve organizational performance, Nurul Jadid apply managerial distribution with a top down and buttom integration scheme, with patterns of synchronization and pooling of resources. This strategy is balanced by reforming the pesantren management infrastructure such as providing a Local Area Network (LAN) for integrating data among many institutions, optimalizing websites, on-line services to santri and wali santri, such as SMS Gateway, e- payment and e-budgeting. Third, to maintain the values of Islamic boarding school in the dynamics of information technology-based quality management, Nurul Jadid Islamic boarding school always strives to be consistent in carrying out its education system based on the basic values of the pesantren through the internalization of the trilogy of santri and the five awareness.